An adaptive variant of TRIB2, rs1057001, is associated with higher expression levels of thermogenic genes in human subcutaneous and visceral adipose tissues - Nakayama, Kazuhiro (J Physiol Anthropol, 2017)
BACKGROUND: An obesity-related single-nucleotide polymorphism (SNP) of the Tribbles pseudokinase 2 gene (TRIB2) was shown to have underwent adaptive evolution in the last glacial period, suggesting a selective advantage of this SNP in human populations in cold environments. In order to verify this hypothesis, the effect of the TRIB2 SNP on the expression of genes involved in adaptive thermogenesis was tested using messenger RNAs prepared from adipose tissues of Japanese adults. METHODS: Complementary DNA was prepared from subcutaneous adipose tissues (SAT) and visceral adipose tissues (VAT) obtained from 48 Japanese adults. Transcript levels of 15 selected genes, including five genes that are upregulated in development of thermogenic adipocytes, were measured by using real-time polymerase chain reaction. Differences in transcript levels between the TRIB2 SNP genotype groups (AA genotype versus AT + TT genotype) were assessed using t test. RESULTS: Of the five thermogenic genes, DIO2, CIDEA, PPARGC1A, and PRDM16 showed significantly higher transcript levels in SAT of individuals with the AA genotype relative to those with the AT + TT genotype (P < 0.05). However, only 2 out of the 10 non-thermogenic genes exhibited differences in transcript levels according to genotype. Additionally, in silico prediction indicated that this SNP likely affects the expression of nearby genes including TRIB2. CONCLUSION: The higher expression levels of thermogenic genes in individuals homozygous for the adaptive variant of TRIB2 SNP suggest a greater propensity for induction of thermogenesis in adipose tissues in cold environments.